ACHIEVING CUSTOMER SATISFACTION THROUGH CUSTOMER LOYALTY AND CUSTOMER EXPERIENCE: SURVEY OF GO-RIDE MULAWARMAN CUSTOMERS - Mukhlis Mukhlis; Herning Indriastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Customer loyalty as intervening variable between customer experience and customer satisfaction on survey of Go-Ride on Mulawarman University customers. With Purposive sampling, the total sample is 123 respondents. The data analysis used path analysis. The result showed: (1) there was a direct effect of customer experience on customer satisfaction. (2) there was a direct of customer satisfaction on customer loyalty. (3) there was an indirect effect of customer experience on customer satisfaction with customer loyalty as intervening. This research is expected to be able to create new marketing strategies for e-commerce business in Indonesia.